Public Protection and Disaster Relief Planning Using Terrestrial Trunked Radio in West Java - Ahmad Riza, Tengku; Mulyana, Asep; Munadi, Rendy (JOIV : International Journal on Informatics Visualization, 2022)
This research aims to implement Public Protection and Disaster Relief (PPDR) planning using Terrestrial Trunked Radio (TETRA) in the West Java area. This plan will work at frequencies 806-821 MHz and 851-866 MHz (bandwidth of 15 MHz). PPDR planning study using TETRA in West Java with a total area of 37,315 Km2. This TETRA planning study uses the simulation method. Simulation using ATOLL software using parameters used by the West Java Regional Police (Polda) because it follows the conditions of the province of West Java. This plan does three things, firstly plans the coverage area to determine the number of base stations by looking for the link power budget and MAPL, followed by finding the cell radius value, secondly planning the network capacity to be used by following the assumptions and predictions of the TETRA mobile station (ms), and the third is planning the frequency spectrum. The three methods are tested and validated using Atoll software simulation. The planning results for the West Java region required 58 sites (base station). The required channels are 94 channels, while from 15 MHz, TETRA digital radio trunking bandwidth provides 600 channels so that TETRA digital trunking radio can be implemented in West Java. In the future, this TETRA radio trunking plan can be implemented in other provinces in Indonesia and even be expanded to all regions in Indonesia to handle disasters